Handbook of fingerprint recognition - Maltoni, Davide (Springer, 2009)
Provides coverage of the major concepts, topics, and security methods associated with fingerprint recognition. This work features chapters covering sensor technology, performance evaluation, standards, and securing fingerprint systems. It is suitable for biometric security professionals, researchers, developers and systems administrators.- Resumé vydavatel